The promise and challenge of eHealth interventions...Proceedings of the 2nd Scientific Meeting of the American Academy of Health Behavior, March 24-27, 2002, Napa Valley, CA - Atkinson NL; Gold RS (American Journal of Health Behavior)
OBJECTIVE: To discuss how health behavior researchers can use the Internet to study and intervene on health behavior. METHODS: Describe how the Internet is increasingly able to offer a viable medium for health behavior intervention and the challenges and opportunities inherent in conducting online interventions and research. RESULTS: The challenges of eHealth include coping with the additional demands of development, finding ways to reach 'hard-to-reach' audiences, and maintaining privacy and security while monitoring participant use. CONCLUSIONS: Health behavior researchers and interventionists need to learn to apply eHealth tools to extend their ability to study and influence health behavior.